ANALISIS PEMAHAMAN HASIL BELAJAR PESERTA DIDIK PADA MATERI BIOLOGI DI SMA MUHAMMADIYAH KEDAWUNG - Adi Firdarahman Sanjaya; Fina Durrotun Na'maus Sholihah; Lilis Nurkholizah; Evi Roviati (TUNAS : Jurnal Pendidikan Biologi, 2025)
This study aims to determine students’ level of understanding in Biology learning and to describe the challenges and efforts made by teachers to improve student learning outcomes. The research employed a qualitative method with a descriptive approach, intended to provide an in-depth depiction of the learning phenomenon. Data collection techniques included questionnaires, interviews, and direct classroom observations. The results showed that 72.2% of students found it relatively easy to understand the Biology material being taught, while 27.8% of students still experienced difficulties in comprehension. Furthermore, 83.3% of students expressed interest and enjoyment in studying Biology. However, several obstacles were identified in the learning process, including students’ mindsets that perceive Biology as a difficult subject, a lack of reading interest, and limited learning support facilities. To overcome these challenges, teachers implemented various strategies such as using diverse teaching methods, setting clear learning goals, and establishing classroom rules that foster a conducive learning environment. This study concludes that creative and adaptive teaching approaches are essential to optimally enhance students’ understanding of Biology material.